The Degree Of Availability of Skills Needed to Build and Employ Electronic Exams for Faculty Members at the University of Jeddah in Light of the Global Trend in E-Learning - Ali bin Muhammad; Al-Kalthmi Al-Shehri; Majed Abdallah Al Harthi (STAI Miftahul Ula Nganjuk, 2021)
This study aims at identifying the degree of availability of skills needed to build and employ electronic exams for faculty members at the University of Jeddah in light of the global trend in e-learning. The study used the descriptive and analytical approach and used a scale applied to a sample of (297) faculty members from the University of Jeddah in the Kingdom of Saudi Arabia. The results of the study concluded that the skills needed to build electronic exams for faculty members had a high degree, with a mean score of (3.45) and a standard deviation of (0.444). The results revealed that the necessary skills to employ electronic exams had a high degree of response, with a mean score of (3.45) and a standard deviation of (0.789). The study recommends conducting training courses for faculty members at the University of Jeddah on building electronic exams and attracting experts to train faculty members on the methods of employing electronic exams.